可见光通信中无人机搜寻通信光源的优化方法 = Optimization methods for UAVs to search light source in VLC - Xiao, Hua (2024)
提 出 了 一 种 解 决 无 人 机（Unmanned aerial vehicle，UAV）在 可 见 光 通 信（Visible‐light communication， VLC）中光源定位不准确的方法，该方法基于扩大及规律缩小搜索路径的方法，最终找到光源以及最佳通信位 置。为了提高本方法的搜索成功率（η），本文针对通信光源的光分布对 η、搜索总路程的影响，以及光电探测 器的探测位置、探测接收角对接收光功率、η 的影响作出了分析。得到了在满足 UAV 探测功率阈值的条件下，光源提供的三维覆盖范围随光源朗伯系数的变化情况，可用于预估 UAV 在不同发光条件下的 η。以等边六边形搜索路径为例，在理想朗伯体条件下，UAV 在光源覆盖半径最大为 0.78 m 时，η 最高可高达 0.74。本方法理论上避免了 UAV 定位不准确导致的无法实现可见光通信的问题，并提出通过优化搜索路径和光源的出光设 计提高光源搜索成功率的方案，为 UAV 可见光通信的实现提出了解决方案。We proposed a method to solve the problem of inaccurate positioning for unmanned aerial vehicles （UAVs）in visible-light communication（VLC）. To sense the light source and find the optimum position for communication，the proposed method expands the search path first and then regularly narrows the search path. In order to improve the success rate（η）of this method，we analyzed the influence of light distribution of the light source on η and the searching distance，and also studied the influence of the position and the receiving angle of the photodetector on the receiving power and η. Three-dimensional（3D）coverage range of the light source，which is determined by the Lambert coefficient and the threshold optical power that can be sensed by the photodetector，is obtained to estimate η of UAV under different circumstances. Taking the searching path of the equilateral hexagonal for example，η can reaches up to 0. 74 with the covering radius of the light source of 0. 78 m by using idea Lambert-distributed light source. The proposed method avoids the inaccurate positioning of UAV，which causes the problem for the UAV to find the communication position in VLC. We theoretically proposed a solution to improve η by light-emission designing and path optimizing，providing the solution for UAVs to realize VLC.